Determinant of Taxpayers Compliance in Paying Motor Vehicle Tax in Demak Region - Damajanti, Anita; Muamanah, Anita; Rosyati, Rosyati (Universitas Semarang, 2023)
This study was conducted to empirically examine determinat factors of taxpayer compliance in paying motor vehicle tax in Demak Region. The variables analyzed in this research are taxpayer awareness, tax sanctions and the quality of tax services on taxpayer compliance. Data collection using a questionnaire method. The sample was calculated using the slovin formula for as many as 100 respondents. Filling out the questionnaire using google form media sent via whatsapp social media and obtained as many as 100 respondents' answers that can be processed data. The analysis method used is ordinary least square regression analysis. The results indicate that taxpayer awareness, tax sanctions, and tax service quality have a significant influence on increasing taxpayer compliance. The coefficient of determination is 48.8%, meaning that the variables of taxpayer awareness, tax penalties, and the quality of tax services can explain the level of tax compliance by 48.8%, and 51.2% is explained by other variables outside the research model.